High-strength steel for chains, highly corrosion-resistant chains for mining, and methods for manufacturing the same.

JP2026534256APending Publication Date: 2026-10-14BAOSHAN IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026518110
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2024-09-27
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0043】 従来の生産技術に比べて、本発明は以下の有益な効果を有する: 1、本発明では、化学成分を合理的に設計するとともに製造方法を最適化し、B元素の添加により鋼の焼入れ性及び機械的性能を向上させ、高価な合金の添加量を低減し、かつ各種合金元素及びそれらの間の相互作用の微細組織、機械的性能への影響を十分に活用することで、優れた総合性能を備えたチェーン用鋼を提供する。チェーン用鋼に対してオンライン焼入れ及び溶融亜鉛めっき処理を行ってチェーンを製造することにより、チェーン用鋼の焼入れ熱処理によって形成された過飽和固溶体中に微細分散した炭化物を析出させ、チェーンの性能を改善できる一方、チェーン用鋼の表面に一定の厚さの亜鉛めっき層(又は亜鉛層ともいう)を形成でき、これによりチェーンが優れた耐腐食性を備える:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026534256000001
    Figure 2026534256000001
  • Figure 2026534256000002
    Figure 2026534256000002
  • Figure 2026534256000003
    Figure 2026534256000003
Patent Text Reader

Abstract

This invention discloses a high-strength chain steel, a highly corrosion-resistant mining chain, and a method for manufacturing the same. The chain steel contains the following chemical components by mass%, including: C: 0.20-0.30%, Si: 0.05-0.6%, Mn: 1.0-1.8%, Cr: 0.4-0.8%, Ni: 0.6-1.2%, Mo: 0.5-0.9%, Ti: 0.01-0.03%, Al: 0.02-0.05%, B: 0.001-0.005%, N: 0.002-0.006%, with the remainder being iron and unavoidable impurities. The highly corrosion-resistant mining chain of this invention not only possesses high strength but also excellent corrosion resistance, making it widely applicable in environments with many corrosive media, such as construction machinery, mines, ships, and marine engineering.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to high-strength chain steel and chain technology, and more particularly to high-strength chain steel, highly corrosion-resistant mining chains, and methods for manufacturing the same. [Background technology]

[0002] Globally, approximately one-sixth of the annual steel production is lost due to corrosion each year. In China, the direct economic loss due to steel corrosion exceeds 10 billion yuan annually. Furthermore, steel corrosion leads to a reduced service life of steel structures, human casualties and economic losses, and environmental pollution due to the discharge of pollutants. Mining ring chains are important components for mechanized coal mining in coal mines and are mainly used as drive chains on scraper conveyors, transfer machines, coal mining machines, and coal mining machines. During use, they are required to have high strength, toughness, fatigue resistance, and wear resistance. Currently, the steel used for mining ring chains that is universally adopted in the coal mining industry is generally the mining chain steel grade in "GB / T 10560-2017 Mining Welded Ring Chain Steel," and among these, high-strength mining ring chain steel is most widely applied, mainly grades such as 23MnNiMoCr54 steel (also abbreviated as 54 steel). Furthermore, in response to the demands of actual applications, major steel mills in China are developing a range of high-strength steels for mining chains to meet the diverse needs of downstream users.

[0003] A Chinese patent with publication number CN110714164A (publication date: January 21, 2020, title: "High-quality Cr54 steel for coal mine annular chains and method for manufacturing the same") discloses a high-quality Cr54 steel for coal mine annular chains that ensures the welding performance of the chain steel and improves the resistance of the chain steel to cold and hot brittleness by introducing carbon equivalent, cold cracking susceptibility coefficient, and hot cracking susceptibility coefficient.

[0004] A Chinese patent with publication number CN104532143A (publication date: April 22, 2015, title: "Large-grade, high-strength steel for mining chains and method for manufacturing the same") discloses an improved large-grade steel for mining chains with a diameter of 40-100 mm, yield strength ≥ 980 MPa, tensile strength ≥ 1180 MPa, elongation ≥ 13%, cross-sectional shrinkage rate ≥ 50%, and Charpy impact absorption energy at room temperature > 100 J.

[0005] Furthermore, some technologies optimize steel materials based on the composition of 54 steel. For example, a Chinese patent with publication number CN111101078A (publication date: May 5, 2020, title: "Nickel-free high-strength annular chain steel for mining and method of production thereof") discloses a nickel-free high-strength annular chain steel for mining that significantly reduces production costs while ensuring mechanical performance by reducing the content of the precious metal element Ni alloy and increasing the content of C, Si, Cr, and Mo alloy elements.

[0006] By referring to the prior art described above and combining it with many current improvements, those skilled in the art have found that high-strength steel for mining chains can be manufactured primarily by optimizing the composition of the steel, thereby improving the strength and wear resistance of mining chains manufactured using this steel and achieving a long service life.

[0007] However, in actual applications, coal mines often have humid working environments. High-strength mining chains are inevitably affected by environmental corrosion during use. Furthermore, current high-strength mining chains have high stress levels and are relatively sensitive to stress corrosion, making them prone to fracture due to corrosion fatigue during use (frequent fractures due to low-load brittleness occur within a few days, or even a few months at most), which leads to premature failure of the mining chains.

[0008] Based on this, the present invention is expected to yield a new steel for mining chains. This steel for mining chains not only has excellent overall performance and high strength, but can also achieve excellent high strength and toughness at a relatively low alloy cost, and the chains after plating have excellent corrosion resistance, effectively solving the problem that affects the service life of existing mining chains due to an imbalance in strength, toughness, ductility and corrosion resistance. [Overview of the project] [Problems that the invention aims to solve]

[0009] To address the problem of existing chains having an unbalanced combination of strength, toughness / ductility, and corrosion resistance, which affects their service life, the present invention aims to provide a high-strength chain steel, a highly corrosion-resistant mining chain, and a method for manufacturing the same. Chains manufactured by combining this high-strength chain steel, which has a reduced amount of expensive alloy additives, with a special plating process not only excel in overall performance such as high strength and toughness, but also in corrosion resistance, making them widely applicable in environments with many corrosive media, such as construction machinery, mines, ships, and marine engineering. [Means for solving the problem]

[0010] To achieve the above objectives, the present invention employs the following technical solutions: A first embodiment of the present invention provides a chain steel comprising, in mass%, the following chemical components: C: 0.20-0.30%, Si: 0.05-0.6%, preferably 0.15-0.6%, Mn: 1.0-1.8%, Cr: 0.4-0.8%, Ni: 0.6-1.2%, Mo: 0.5-0.9%, Ti: 0.01-0.03%, Al: 0.02-0.05%, B: 0.001-0.005%, N: 0.002-0.006%, with the remainder being iron and unavoidable impurities.

[0011] Preferably, the chemical composition of the steel for chains satisfies the following formula: 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≧6, more preferably 6≦30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≦24.43 (wherein each element symbol is substituted with the value of the corresponding element in mass %).

[0012] Preferably, in the unavoidable impurities, P≦0.015%, S≦0.01%, O≦0.002%.

[0013] Preferably, the microstructure of the steel for chains is acicular martensite.

[0014] Preferably, the properties of the steel for chains are such that the yield strength Rp 0.2 ≧1050MPa, the tensile strength R m ≧1200MPa, the elongation A≧14%, the reduction of area Z≧50%, and the Charpy impact absorbed energy A at -20°C kv ≧60J is satisfied.

[0015] A second aspect of the present invention provides a chain comprising the above-described steel for chains and a zinc plating layer applied on the steel for chains.

[0016] Preferably, the thickness of the zinc plating layer in the chain is 10 to 150 μm, preferably 40 to 150 μm.

[0017] Preferably, the microstructure of the steel for chains in the chain is tempered martensite and carbides finely dispersed between lamellae.

[0018] Preferably, the properties of the chain are such that the yield strength Rp 0.2 ≧1050MPa, the tensile strength R m ≧1200MPa, the elongation A≧14%, the reduction of area Z≧50%, the Charpy impact absorbed energy A at -20°C kv ≧60J is satisfied, and the corrosion rate after 120 hours of 5% NaCl neutral salt spray corrosion test is 0.2g / m 2 ·h or less.

[0019] A third embodiment of the present invention involves the following steps: S1: Smelting and casting molten steel to obtain a cast slab; S2: Hot rolling of the cast slab to a compression ratio of 10 or more; S3: Forming and welding of chain links; S4: A quenching heat treatment in which the heating temperature is 840-980°C, preferably 850-950°C, the holding time is 1-4 hours, preferably 1-3 hours, followed by quenching by water cooling; S5: Perform pre-treatment with pickling to obtain steel for chains; S6: After preheating the chain steel following the pickling pretreatment, hot-dip galvanizing is performed to obtain a chain containing the chain steel and the galvanized layer formed on the surface of the chain steel (wherein the temperature difference between the preheating temperature of the preheating treatment and the hot-dip galvanizing solution used for the hot-dip galvanizing is set to -30 to 30°C). The present invention provides a method for manufacturing the above chain, which sequentially includes the elements described above.

[0020] Preferably, in step S1, the smelting includes electric furnace or converter smelting, LF refining, VD or RH vacuum treatment. A continuous casting process is employed in the casting.

[0021] Preferably, the vacuum treatment time for the VD or RH vacuum treatment is 10 to 20 minutes. In the casting process, the superheating of the molten steel in the tundish is controlled to 15 to 40°C.

[0022] Preferably, in step S2, during the hot rolling process, the heating temperature of the cast slab is ≥ 1150°C, the heating time is 3 to 6 hours, and the rolling completion temperature is ≥ 850°C, and after rolling, air cooling or slow cooling is employed.

[0023] Preferably, in step S6, the preheating temperature is 400 to 550°C and the preheating time is 0.5 hours or more. The temperature of the molten zinc plating solution used during the molten zinc plating is 400 to 530°C.

[0024] Preferably, the thickness of the zinc plating layer is 10 to 150 μm, preferably 40 to 150 μm.

[0025] Preferably, the microstructure of the steel for chains in the chain obtained in step S6 is tempered martensite and carbides finely dispersed between lamellae.

[0026] Preferably, the performance of the chain is such that the yield strength Rp 0.2 ≥ 1050 MPa, the tensile strength R m ≥ 1200 MPa, the elongation A ≥ 14%, the reduction of area Z ≥ 50%, and the Charpy impact absorbed energy A at -20°C kv ≥ 60 J, and the corrosion rate after 120 h of 5% NaCl neutral salt spray corrosion test is 0.2 g / m 2 ·h or less.

[0027] In the high-strength chain steel of the present invention, the design mechanism of each chemical element is as follows. In this specification, unless otherwise specified, the element content is expressed in mass%.

[0028] C: C is an essential element for securing the strength of steel materials. When the C content in steel is increased, the transformation ability of steel to non-equilibrium structures is enhanced, thereby significantly improving the strength of steel. In the present invention, the quenching heat treatment process suppresses the diffusion of C element in steel and forms shear-type martensite transformation, so as to significantly improve the strength of steel. However, it is desirable that the content of C element in steel is not too high. If the C content is too high, it will adversely affect both the ductility and toughness of steel, and significantly increase the carbon equivalent of the material, thus deteriorating the welding performance of the steel material. Based on this, in the high-strength chain steel of the present invention, the content of C element in mass% is controlled to 0.20 to 0.30%.

[0029] Si: Si elements can form solid solutions in steel, resulting in solid solution strengthening and significantly improving the yield strength, fatigue strength, and hardness of the steel. However, Si has low solubility in cementite, and it is desirable that the Si content in the steel not be too high. If the Si content in the steel is too high, it will form a bainite structure that does not contain carbides, and will also increase the brittleness of the steel. Based on this, in the high-strength chain steel of the present invention, the Si content by mass percentage is controlled to 0.05 to 0.6%, preferably 0.15 to 0.6%.

[0030] Mn: The element Mn enhances the stability of austenite in steel and also improves the hardenability of the steel. Furthermore, Mn strengthens the martensite in steel through solid solution strengthening, further improving the strength of the steel. However, care must be taken not to make the Mn content in the steel too high. If the Mn content in the steel is too high, austenite grains will grow more easily during quenching heating, and harmful elements will be promoted to segregate at the crystal boundaries. Based on this, in the high-strength chain steel of the present invention, the Mn content by mass is controlled to 1.0 to 1.8%.

[0031] Cr: Adding an appropriate amount of Cr improves the hardenability of steel and has a secondary hardening effect, allowing for the formation of a hardened martensitic structure, which is advantageous for improving the strength of the steel. Furthermore, Cr carbides can delay the growth of crystal grains in the heat-affected zone of welded joints, which is very advantageous for welding steel. Adding appropriate amounts of Cr and Ni elements to steel is advantageous for improving the corrosion resistance of the steel. However, it is also desirable that the Cr content in the steel not be too high. If the Cr content in the steel is too high, a large amount of carbides are generated, segregating at the crystal boundaries, reducing the toughness of the material, significantly increasing the carbon equivalent, and degrading the welding performance of high-strength chain steel. Based on this, in the high-strength chain steel of the present invention, the mass% content of Cr is controlled to 0.4-0.8%.

[0032] Ni:Ni, as one of the main strengthening elements, can exist in solid solution in steel and can infinitely solid-solve with iron. When Ni and Cr are used together, the hardenability of the steel can be significantly improved. Furthermore, by adding an appropriate amount of Ni to the steel, the carbon content at the eutectoid point can be reduced, ferrite can be strengthened, and pearlite can be refined and increased, thereby improving the strength of the steel without significantly affecting its ductility. Ni increases the fatigue resistance of the steel, reduces its susceptibility to notches, lowers the low-temperature embrittlement transformation temperature of the steel, and improves the impact toughness of the steel. However, Ni is also a valuable alloying element, and adding it in excess increases the alloy cost. Therefore, in the high-strength chain steel of this invention, the mass% content of Ni is controlled to 0.6 to 1.2%.

[0033] Mo: The element Mo mainly exists in steel in a solid solution state and can provide a solid solution strengthening effect, which is advantageous for improving the hardenability of steel materials and facilitates the formation of martensite during the quenching process. However, it is also desirable that the Mo content in steel not be too high. If the Mo content in steel is too high, it significantly increases the carbon equivalent of the material, which is detrimental to the weldability of the steel material. Furthermore, Mo is a valuable alloying element, and adding excessive Mo leads to an increase in alloy costs. Based on this, in the high-strength chain steel of the present invention, the mass percentage content of the element Mo is controlled to 0.5 to 0.9%.

[0034] Ti: The element Ti has an extremely strong affinity for nitrogen, oxygen, and carbon, and has a high precipitation temperature, making it an effective element for fixing nitrogen and carbon. By forming a fine precipitate phase in steel, it can improve the strength and toughness of the steel, especially its impact toughness at low temperatures. However, if the Ti content in the steel is too high, coarse, angular TiN particles are formed during the smelting process, reducing the impact toughness of the steel. Therefore, in the high-strength chain steel of the present invention, the Ti content is controlled to 0.01-0.03%.

[0035] Al:Al's main functions are deoxidation and nitrogen fixation, and A1N, formed by the bonding of A1 and N, can effectively refine the crystal grains. However, it should be noted that the Al content in the steel should not be excessively high. If the Al content in the steel is too high, it will affect the casting performance of the steel and further impair the toughness of the steel. Based on this, in the high-strength chain steel of the present invention, the Al content by mass percentage is controlled to 0.02-0.05%.

[0036] The main function of B is to increase the hardenability of steel, enhance the strength of steel after quenching and tempering, and slightly improve ductility, thereby saving other rare and valuable metals such as nickel, chromium, and molybdenum. However, element B is relatively reactive and has a strong affinity for elements such as oxygen and nitrogen, forming boron oxide and boron nitride, which easily degrades element B, greatly increasing the variation in the hardenability of steel and affecting the stability of the steel's performance. B is a highly reactive and segregating element, easily segregating at grain boundaries and causing temper brittleness, which adversely affects the toughness of the steel. Therefore, in the high-strength chain steel described in the present invention, the content of element B is controlled to 0.001 to 0.005%.

[0037] N:N is an austenite-forming element, but it is also an MX-type precipitate-forming element, and thus plays a role in grain refinement. However, in B-containing steel, the N element in the steel bonds with the B element, causing the B in the steel to lose its alloying properties. To avoid the depletion of B element by the N element, it is necessary to strictly control the N element content in the steel. Therefore, in the high-strength chain steel of the present invention, the N element content by mass is controlled to 0.002 to 0.006%.

[0038] In this invention, the main alloying elements are rationally designed, the hardenability and mechanical properties of the steel are improved by adding element B, the amount of expensive alloys added is reduced, and the influence of various alloying elements and their interactions on the microstructure and mechanical properties is fully utilized, thereby giving the high-strength chain steel of this invention excellent overall performance.

[0039] In a preferred embodiment, in the chemical composition of the chain steel, element B, Cr, Ni, and Mo are given by the following formula: 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≧6, preferably 6≦30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≦24.43 (wherein the formula, the symbol for each element is replaced with the number preceding the mass % of the corresponding element).

[0040] In the high-strength chain steel of the present invention, Cr, Ni, and Mo are important alloying elements, and each element contributes differently to the strength, toughness, and hardenability of the chain steel. However, adding excessively expensive alloying elements significantly increases the cost of the steel. Therefore, in the chain steel of the present invention, by adding appropriate amounts of Cr, Ni, and Mo, interactions occur with trace amounts of B added to the steel. When the relationship between B and Cr, Ni, and Mo satisfies 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≧6, B dissolves in the base material, segregates at the austenite grain boundaries, enhances the stability of the austenite, increases the hardenability of the steel during the heat treatment process for manufacturing the chain, and gives the steel good overall performance such as high strength and high toughness. If the relationship between element B and elements Cr, Ni, and Mo satisfies 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)<6, then the content of element B added to the steel is low, and it cannot improve the hardenability of the steel. In this case, expensive alloying elements must be added to ensure that the chain steel obtains good high strength and toughness performance in the quenching heat treatment and hot-dip galvanizing processes, which increases the production cost of the chain.

[0041] In the chain steel of the present invention, the unavoidable impurities are required to be P ≤ 0.015%, S ≤ 0.01%, and O ≤ 0.002%. Here, P, S, and O are all impurity elements in steel, and where technical conditions allow, the content of impurity elements in the material should be reduced as much as possible in order to obtain chain steel with better performance and higher quality. In the chain steel of the present invention, P and S are both unavoidable harmful impurity elements in steel, and both degrade the performance of the steel. Although P can improve the weather resistance of steel, the overall side effects are greater, so in the present invention, P is controlled to satisfy P ≤ 0.015% and S is controlled to satisfy S ≤ 0.01%. Accordingly, in the present invention, the impurity element O can form oxides and composite inclusions together with deoxygenating elements such as Ti, B, and Al in the steel, which is detrimental to the performance of the steel material. Therefore, in the present invention, O is controlled to satisfy O ≤ 0.002%.

[0042] Of course, in some other embodiments, other harmful elements such as As, Pb, Sn, Sb, and Bi may be present in the steel. The content of these harmful elements should be reduced as much as possible under the requirements of national laws, regulations, and standards. [Effects of the Invention]

[0043] Compared to conventional production technologies, the present invention has the following beneficial effects: 1. In this invention, by rationally designing the chemical composition and optimizing the manufacturing method, improving the hardenability and mechanical performance of the steel by adding element B, reducing the amount of expensive alloys added, and fully utilizing the influence of various alloying elements and their interactions on the microstructure and mechanical performance, a chain steel with excellent overall performance is provided. By manufacturing a chain by performing online quenching and hot-dip galvanizing treatment on the chain steel, finely dispersed carbides can be precipitated in the supersaturated solid solution formed by the quenching heat treatment of the chain steel, thereby improving the performance of the chain. At the same time, a zinc plating layer (also called a zinc layer) of a certain thickness can be formed on the surface of the chain steel, thereby providing the chain with excellent corrosion resistance.

[0044] 2. The present invention improves the corrosion resistance of a chain by applying a zinc plating layer to the surface of the chain steel, thereby blocking contact between the corrosive medium and the chain steel. After the coating in some areas of the chain wears away, the zinc layer in other areas also provides anodic protection, suppressing corrosion during the chain's use and further extending its service life.

[0045] 3. The high-strength chain steel of the present invention has a rational chemical composition and process design, a wide process window, and enables commercial production through mass production:

[0046] 4. The high-strength chain steel and chains of the present invention achieve excellent high strength, high toughness, and good corrosion resistance with low composition, and can be manufactured into high-strength corrosion-resistant structural components and high-performance industrial chains for various mining and mooring applications, and can be widely applied in situations where high-strength, high-toughness, and high-corrosion-resistant steel materials are required in construction machinery, mining, and marine engineering, etc.

[0047] 5. The highly corrosion-resistant mining chain manufactured from the chain steel of the present invention not only possesses high strength, toughness, and ductility, but also excellent corrosion resistance, giving it a very wide range of potential applications. [Modes for carrying out the invention]

[0048] To better understand the above technical proposal of the present invention, the technical proposal of the present invention will be further described below with reference to examples.

[0049] The present invention provides a chain steel comprising the following chemical components by mass%, C: 0.20-0.30%, Si: 0.05-0.6%, preferably 0.15-0.6%, Mn: 1.0-1.8%, Cr: 0.4-0.8%, Ni: 0.6-1.2%, Mo: 0.5-0.9%, Ti: 0.01-0.03%, Al: 0.02-0.05%, B: 0.001-0.005%, N: 0.002-0.006%, with the remainder being iron and unavoidable impurities.

[0050] This invention rationally designs the main alloying elements, improves the performance of the steel by adding element B, reduces the amount of expensive alloys added, and fully utilizes the influence of various alloying elements and their interactions on the microstructure and mechanical properties, thereby precisely controlling the microstructure of the steel according to the present invention. This ensures that when the chain steel of the present invention is hot-dip galvanized to manufacture a chain, a mixed microstructure of tempered martensite + finely dispersed carbides between the lamellae is formed in the chain steel. As a result of this microstructure, the chain of the present invention possesses a balance of high strength, toughness, and ductility, as well as good wear resistance and fatigue resistance.

[0051] In a specific example, the chemical composition of the chain steel is given by the following formula: 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≧6, preferably 6≦30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≦24.43 (wherein the formula, the symbol for each element is replaced with the number preceding the mass % of the corresponding element).

[0052] In this invention, Cr, Ni, and Mo are important alloying elements, and each element contributes differently to the strength, toughness, and hardenability of high-strength chain steel. However, adding excessive alloying elements significantly increases the cost of the steel. Therefore, in this invention, by adding appropriate amounts of Cr, Ni, and Mo to the steel, interactions occur with trace amounts of B added to the steel. When the relationship between B and Cr, Ni, and Mo satisfies "30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)≧6", B can be dissolved in the base material, segregating at the austenite grain boundaries to enhance the stability of the austenite, increasing the hardenability of the steel during the quenching heat treatment process for manufacturing chain steel, and giving the steel good overall performance such as high strength and high toughness. If 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo)<6, the content of element B added to the steel is low, and it cannot improve the hardenability of the steel. In order to ensure that chain steel obtains good high strength and high toughness in the quenching and hot-dip galvanizing processes, it is necessary to add expensive alloying elements, which increases the production cost of the chain.

[0053] In this invention, elements P, S, and O are all impurity elements in steel, and where technical conditions permit, the content of impurity elements in the material should be reduced as much as possible in order to obtain high-strength steel with better performance and superior quality. In particular, elements P and S are both unavoidable harmful impurity elements in steel and both degrade the performance of the steel. Element P can improve the weather resistance of steel, but overall its side effects are greater. Therefore, for unavoidable impurities, P ≤ 0.015% and S ≤ 0.01% are set. Accordingly, impurity element O can form oxides and composite inclusions together with deoxidizing elements such as Ti, B, and Al in the steel, which is detrimental to the performance of the steel, so O ≤ 0.002% is set.

[0054] In a specific example, the microstructure of the chain steel is needle-shaped martensite. The microstructure of the chain steel in a chain formed by quenching heat treatment and hot-dip galvanizing of the high-strength chain steel is tempered martensite and carbides finely dispersed between the lamellae.

[0055] The performance of this high-strength steel for mining chains is as follows: yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A ≥14%, cross-sectional shrinkage Z ≥50%, Charpy impact absorption energy A at -20℃ kv The condition is met by ≥60J.

[0056] Chains manufactured by applying hot-dip galvanizing to the surface of the steel used for the chain showed a corrosion rate of 0.2 g / m after 120 hours of 5% NaCl neutral salt spray corrosion testing. 2 It is less than or equal to h.

[0057] The present invention relates to a chain made of the above-mentioned chain steel, wherein the performance is such that the yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A ≥14%, cross-sectional shrinkage Z ≥50%, Charpy impact absorption energy A at -20℃ kv The sample satisfies the requirement of ≥60J and exhibits a corrosion rate of 0.2 g / m² after 120 hours of 5% NaCl neutral salt spray corrosion testing. 2 Provide a chain that is less than or equal to h.

[0058] Furthermore, the present invention provides a method for manufacturing the above-mentioned highly corrosion-resistant chain for mining. This method is easy to produce, and the resulting chain has excellent high strength, high toughness, and good corrosion resistance.

[0059] The present invention provides a chain steel and a method for manufacturing a chain, which specifically includes the following steps: S1. Smelting and casting molten steel to obtain a cast slab: Specifically, the smelting operation includes smelting in an electric furnace or converter, LF refining, and VD or RH vacuum treatment. That is, smelting in an electric furnace or converter is employed, followed by LF refining, VD or RH vacuum treatment. Here, the vacuum treatment time is set to 10-20 minutes, and after the chemical composition meets the requirements for chain steel, the steel is tapped and cast. Accordingly, in the casting process, a continuous casting process is employed to cast slabs, the superheating of the molten steel in the tundish is controlled to 15-40°C, and finally a slab with chemical composition that satisfies the requirements for chain steel is obtained. S2. Hot rolling is performed so that the compression ratio of the cast slab is 10 or more: Specifically, the slab is first heated in a heating furnace, then removed from the furnace, phosphorus is removed with high-pressure water, and then rolling is started to roll the slab into round steel bars of the product size. The heating temperature of the slab is controlled to be ≥1150°C, the heating time to be 3-6 hours, and the rolling completion temperature to be ≥850°C. After rolling, it is air-cooled or slowly cooled to room temperature. Here, the compression ratio of the slab is controlled to be ≥10 during the rolling process. The standard product size of the resulting round steel bars is Φ30-150mm. S3. Forming and welding of chain links: After cutting round steel to a predetermined length, the links are formed into single links using a ring forming machine, and then welded to a complete annular chain base material by flash welding. S4. Quenching heat treatment: Here, the heating temperature for the quenching heat treatment is set to 850-950°C, the holding time to 1-3 hours, and quenching is performed by water cooling after heating. Specifically, a chain-shaped base material formed and welded to a chain link is subjected to quenching heat treatment. The quenching heat treatment is performed at a heating temperature of 850-950°C, with a holding time of 1-3 hours, followed by quenching by water cooling. When the chain-shaped base material is heated to a high temperature, fine austenite crystal grains are formed, and the austenite grain size is grade 7 or higher. After quenching by water cooling, the structure of the chain-shaped base material transforms from the austenite structure formed at high temperature to a fine, needle-like martensite structure. S5. Pre-pickling treatment: Pre-pickling treatment is performed on the chain-shaped base material after quenching heat treatment to remove the oxide film on the surface of the chain-shaped base material after quenching and obtain chain steel. Preferably, a layer of flux solution is applied to the surface of the chain steel to maintain a certain active state on the surface of the chain steel after pre-pickling treatment, suppressing oxidation of the chain steel in the subsequent pre-heating treatment process and improving the adhesion between the zinc plating layer and the chain steel. The flux solution used in this invention is commonly used in zinc plating in this field and is commercially available. S6, after hot-dip galvanizing and pickling pretreatment, the chain steel is subjected to preheating treatment and then hot-dip galvanizing to obtain a chain containing the chain steel and the galvanized layer formed on the surface of the chain steel. Here, the temperature difference between the preheating temperature of the preheating treatment and the hot-dip galvanizing solution used during hot-dip galvanizing is controlled to -30 to 30°C. Specifically, in order to prevent problems such as zinc scattering during the hot-dip galvanizing process, the chain steel is preheated and then further hot-dip galvanized to obtain a highly corrosion-resistant mining chain. Here, the temperature difference between the preheating temperature of the chain and the hot-dip galvanizing solution used during hot-dip galvanizing is controlled to -30 to 30°C. Here, the preheating temperature is set to 400 to 550°C, the preheating time to 0.5 hours or more, the temperature of the hot-dip galvanizing solution used during hot-dip galvanizing is set to 400 to 530°C, and the thickness of the zinc plating layer on the surface of the chain steel is controlled to 10 to 150 μm, preferably 40 to 150 μm.

[0060] During the hot-dip galvanizing process, fine carbides begin to precipitate within the supersaturated needle-shaped martensitic structure formed after quenching of the chain steel. While the strength of the chain steel slightly decreases, its elongation and impact toughness begin to increase. Here, the fine needle-shaped martensitic structure is advantageous for the precipitation of finely dispersed carbides from the chain steel during hot-dip galvanizing, resulting in a chain with excellent strength and toughness.

[0061] The microstructure of the chain steel in the above-mentioned highly corrosion-resistant mining chain consists of tempered martensite and carbides finely dispersed between the lamellae.

[0062] The performance of the above-mentioned highly corrosion-resistant mining chain is measured by its yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A ≥14%, cross-sectional shrinkage Z ≥50%, Charpy impact absorption energy A at -20℃ kv The sample satisfies the requirement of ≥60J and exhibits a corrosion rate of 0.2 g / m² after 120 hours of 5% NaCl neutral salt spray corrosion testing. 2 It is less than h.

[0063] In this invention, the chemical composition is rationally designed and the manufacturing process is optimized, and the influence of various alloying elements and the chain steel and chain manufacturing process on the microstructure is fully utilized to precisely control the microstructure of the chain steel. Needle-shaped martensitic structures are formed in the chain steel obtained by quenching heat treatment, and by hot-dip galvanizing the chain steel, finely dispersed carbides are precipitated during the hot-dip galvanizing process, improving the strength and toughness of the chain. At the same time, a zinc plating layer of a certain thickness can be formed on the surface of the chain steel, improving the corrosion resistance of the chain.

[0064] In the chain manufacturing method of the present invention, by combining the conventional chain quenching and tempering process with the hot-dip galvanizing process, the chain tempering process is omitted, and the process of precipitation of carbides in the chain steel during the hot-dip galvanizing process is fully utilized to achieve efficient production of high-strength, corrosion-resistant chains. As a result, the high-strength chain possesses a balance of high strength, toughness, and ductility, as well as good corrosion resistance.

[0065] The following provides further details, with specific examples, of the high-strength chain steel, highly corrosion-resistant mining chain, and manufacturing method of the present invention. Note that the following examples are merely illustrative to illustrate specific embodiments of this disclosure and do not limit the scope of protection of this disclosure in any way. [Examples]

[0066] Examples 1-6 In accordance with the contents shown in Tables 1, 2-1, and 2-2, the following steps were sequentially adopted to obtain the high-strength chain steel and high-corrosion-resistant mining chains of Examples 1 to 6: (1) Slabs were obtained by smelting and continuous casting according to the chemical composition shown in Table 1 below. For smelting, an electric furnace or converter was used, and LF refining, VD or RH vacuum treatment was performed, with a vacuum treatment time of 10 to 20 minutes, and the steel was tapped after the composition met the requirements. Subsequently, the steel was cast into slabs by continuous casting, and during the continuous casting process, the superheating of the molten steel in the tundish was controlled to 15 to 40°C. (2) Hot rolling: After heating the cast slab in a heating furnace, phosphorus was removed with high-pressure water and processed to obtain round steel of the product size. The specified range for the rolled product size was Φ30 to 150 mm, and the compression ratio of the cast slab was controlled to ≥ 10. In the rolling process, after heating the ingot, it was rolled to the product size, the controlled casting slab heating temperature was controlled to ≥ 1150°C, the heating time was 3 to 6 hours, and the rolling completion temperature was ≥ 850°C. After the rolling was completed, it was air-cooled or slowly cooled to room temperature. (3) Forming and welding of chain links: After cutting round steel to a predetermined length, the links were formed into single links using a ring forming machine, and then welded to a complete annular chain base material by flash welding. (4) Quenching heat treatment: Quenching heat treatment was performed on the chain-shaped base material after forming and welding the chain links. The heating temperature for the quenching heat treatment was controlled to 840-980°C, the holding time to 1-4 hours, and then quenching was performed by water cooling. (5) Pre-treatment before pickling: The chain-shaped base material after quenching heat treatment was subjected to pre-treatment before pickling to remove the oxide film on the chain surface. Subsequently, in order to prevent problems such as zinc scattering in the hot zinc plating process, the chain-shaped base material after pre-treatment before pickling was preheated to 400-550°C for a preheating time of 0.5 hours or more. The temperature difference between the preheating temperature of the chain-shaped base material after pre-treatment before pickling and the temperature of the hot zinc plating solution used in the subsequent hot zinc plating was kept within ±30°C. (6) Hot-dip galvanizing: Hot-dip galvanizing was performed on the chain-shaped base material after pre-treatment with pickling and preheating, with the zinc solution temperature set to 400-530°C and the thickness of the zinc plating layer on the chain surface controlled to 10-150 μm, to obtain a chain containing chain steel and a zinc plating layer on the surface of the chain steel.

[0067] The chemical composition designs and related processes for the high-strength chain steel and high-corrosion-resistant mining chains of Examples 1 to 6 all meet the design standard requirements of the present invention.

[0068] Comparative Examples 1-2 The comparative steel materials in Comparative Examples 1 and 2 are product steel materials from different manufacturers, and their chemical composition is as shown in Table 1 below. Their processing processes differ from those of Examples 1 to 6, and the heat treatment processes used for the comparative steel materials in Comparative Examples 1 and 2 adopted parameters recommended by the manufacturers. The specific numerical values ​​are shown in Tables 2-1 and 2-2. Here, the tempering temperature and tempering time in Table 2-2 refer to the tempering processes of Comparative Examples 1 and 2.

[0069] Table 1 shows the chemical composition of the chain steels of Examples 1-6 and the comparative steels of Comparative Examples 1-2.

[0070] [Table 1]

[0071] Table 2-1 shows the specific process parameters in the manufacturing process of the product chains for Examples 1-6 and the comparative chains for Comparative Examples 1-2.

[0072] [Table 2-1]

[0073] Table 2-2 shows the specific process parameters in the manufacturing process of the product chains for Examples 1-6 and the comparative chains for Comparative Examples 1-2.

[0074] [Table 2-2]

[0075] Product chains manufactured in Examples 1-6 and comparative chains from Comparative Examples 1-2 were collected, and further tests were conducted on their performance to obtain the performance of the product chains in each example and comparative example.

[0076] In this invention, neutral salt spray corrosion tests, tensile tests, and impact performance tests were performed on the product chains of Examples 1 to 6 and the comparative chains of Comparative Examples 1 to 2, respectively. The test results are shown in Table 3.

[0077] The specific test methods for the relevant neutral salt spray corrosion test, tensile test, and impact test are as follows: (1) The neutral salt spray corrosion test was performed in the following manner: Round steel pieces with a length of 100 mm were taken from the product chains of Examples 1 to 6 and the comparative chains of Comparative Examples 1 to 2 to be used as salt spray corrosion test pieces. Both ends were sealed with silicone rubber, and a 5 wt% NaCl salt spray corrosion test was performed in accordance with the GB / T10125 standard (test chamber temperature: 35°C, saturated tank temperature: 47°C, corrosion medium: 5 wt.% NaCl aqueous solution, pH = 6.5, test piece was positioned at an angle of 20° from the vertical, test time: 120 h, spray method: continuous spray, salt spray sedimentation rate: 1.5 mL / h·80 cm 2 After the 120-hour neutral salt spray test was completed, the specimens were removed, the silicone rubber at both ends was peeled off, the corrosion products on the surface were removed, and the mass of the dried specimens was recorded as M'. Subsequently, the salt spray corrosion rate R of the specimens for each example and comparative example was calculated: R = (M - M') / (S · T) Here, M is the initial mass of the specimen in grams, M' is the mass of the specimen after removing the corrosion products and drying it in grams, and S is the corrosion test area of ​​the specimen in meters. 2 Here, T is the corrosion time, in units of h, and the salt spray corrosion rate R is in units of g / m 2 It is h.

[0078] Tensile Test: Product chains from Examples 1-6 and comparative chains from Comparative Examples 1-2 were sampled in accordance with the Chinese national standard GB / T 2975, prepared as tensile test specimens, and subjected to tensile performance testing in accordance with the Chinese national standard GB / T 228.1. The yield strength Rp of the product chains from Examples 1-6 and the chains from Comparative Examples 1-2 was determined. 0.2 , tensile strength R m The elongation A and the cross-sectional shrinkage rate Z were measured.

[0079] Impact Test: Product chains from Examples 1-6 and comparative chains from Comparative Examples 1-2 were sampled in accordance with Chinese national standard GB / T 2975, used as impact test specimens, and subjected to impact performance tests in accordance with Chinese national standard GB / T 229. The low-temperature impact energy A of the product chains from Examples 1-6 after plating and the chains from Comparative Examples 1-2 was determined. kv We measured it.

[0080] Table 3 shows the performance parameters of the product chains for Examples 1-6 and the comparative example chains for Comparative Examples 1-2.

[0081] [Table 3]

[0082] As shown in Table 3, the highly corrosion-resistant mining chains in Examples 1 to 6 of the present invention exhibit excellent overall performance and have a yield strength Rp 0.2 The pressure is between 1076 and 1185 MPa, and the tensile strength R m The pressure is 1212-1315 MPa, elongation A ≥ 14%, cross-sectional shrinkage Z ≥ 50%, and Charpy impact absorption energy A at -20°C. kv The pressure was ≥60J. The highly corrosion-resistant mining chains in Examples 1-6 had a neutral salt spray corrosion rate of 0.19 g / m 2 The corrosion rate was less than or equal to 1.5 hours, which is significantly lower than the neutral salt spray corrosion rate of the comparative chains used in Comparative Examples 1 and 2. This indicates that, after undergoing quenching heat treatment and hot-dip galvanizing, the corrosion resistance of the high-strength chain steel of the present invention is clearly superior to that of the existing comparative steel materials used in Comparative Examples 1 and 2.

[0083] As described above, the present invention rationally designs the chemical composition and combines it with conventional chain heat treatment and subsequent zinc plating processes to establish an optimized quenching heat treatment and hot-dip galvanizing process, ultimately yielding a high-performance, corrosion-resistant mining chain. The chain steel of the present invention not only possesses excellent overall performance and high strength, but also an excellent balance of toughness and ductility, and is highly corrosion-resistant after being manufactured into mining chains. This effectively solves the problem of current mining chains having an imbalance in strength, toughness / ductility, and corrosion resistance, which affects their service life. This chain steel can be manufactured into various high-performance industrial chains for mining, mooring, etc., and can be widely applied when high-strength, high-toughness, and high-corrosion-resistant chains are required in construction machinery, mining, and marine engineering.

[0084] Furthermore, all technical features described herein can be freely combined or combined in any way, as long as they do not contradict each other. Various modifications and changes can be made to the present invention, as long as they do not depart from the scope of the invention, and these will be obvious to those skilled in the art. For example, features shown or described in part of one embodiment can be combined with another embodiment to form another embodiment. Therefore, the present invention aims to encompass all changes and modifications that fall within the claims and their equivalent scope.

Claims

1. A chain steel characterized by containing, by mass%, the following chemical components: C: 0.20-0.30%, Si: 0.05-0.6%, preferably 0.15-0.6%, Mn: 1.0-1.8%, Cr: 0.4-0.8%, Ni: 0.6-1.2%, Mo: 0.5-0.9%, Ti: 0.01-0.03%, Al: 0.02-0.05%, B: 0.001-0.005%, N: 0.002-0.006%, with the remainder being iron and unavoidable impurities.

2. The chain steel according to claim 1, characterized in that the chemical composition of the chain steel satisfies the following formula: 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo) ≥ 6, preferably 6 ≤ 30000*B / (300*B+0.7*Ni+2*Cr+5*Mo) ≤ 24.43 (wherein the formula, the symbol for each element is replaced with the numerical value preceding the mass percent of the corresponding element).

3. The chain steel according to claim 1, characterized in that, among the unavoidable impurities, P ≤ 0.015%, S ≤ 0.01%, and O ≤ 0.002%.

4. The chain steel according to claim 1, characterized in that the microstructure of the chain steel is needle-shaped martensite.

5. The performance of the steel for the chain is such that the yield strength Rp 0.2 ≥1050 MPa, tensile strength R m ≥1200 MPa, elongation A ≥14%, cross-sectional shrinkage rate Z ≥50%, Charpy impact absorption energy A at -20°C kv The chain steel according to claim 1, characterized in that it satisfies ≥ 60J.

6. A chain comprising a chain steel according to any one of claims 1 to 5, and a zinc plating layer applied to the chain steel.

7. The chain according to claim 6, characterized in that the thickness of the zinc plating layer is 10 to 150 μm, preferably 40 to 150 μm, and / or the microstructure of the chain steel is tempered martensite and carbides finely dispersed between the lamellae.

8. The performance of the aforementioned chain is such that the yield strength Rp 0.2 ≥1050 MPa, tensile strength R m ≥1200 MPa, elongation A ≥14%, cross-sectional shrinkage rate Z ≥50%, Charpy impact absorption energy A at -20°C kv The sample satisfies the requirement of ≥60J, and the corrosion rate after 120 hours of 5% NaCl neutral salt spray corrosion testing is 0.2 g / m². 2 The chain according to claim 6, characterized in that it is less than or equal to h.

9. The following steps: S1: Smelting and casting molten steel to obtain a cast slab; S2: Hot rolling of the cast slab so that the compression ratio is 10 or more; S3: Forming and welding of chain links; S4: A quenching heat treatment in which the heating temperature is 840 to 980°C, preferably 850 to 950°C, the holding time is 1 to 4 hours, preferably 1 to 3 hours, and quenching is performed by water cooling; S5: Perform pickling pretreatment to obtain steel for chains; S6: After preheating the chain steel following the pickling pretreatment, hot-dip galvanizing is performed to obtain a chain containing the chain steel and the galvanized layer formed on the surface of the chain steel (here, the temperature difference between the preheating temperature of the preheating treatment and the hot-dip galvanizing solution used for the hot-dip galvanizing is controlled to -30 to 30°C). A method for manufacturing a chain according to any one of claims 6 to 8, characterized by including in order the above.

10. In step S1, the smelting includes smelting in an electric furnace or converter, LF refining, VD or RH vacuum treatment, the casting employs a continuous casting process, preferably the vacuum treatment time for the VD or RH vacuum treatment is 10 to 20 mins, and in the casting process, the superheating degree of the molten steel in the tundish is controlled to 15 to 40°C; and / or, In step S2, during the hot rolling process, the heating temperature of the cast slab is set to ≥ 1150°C, the heating time to 3 to 6 hours, and the rolling completion temperature to ≥ 850°C. After rolling, air cooling or slow cooling is employed; and / or, The manufacturing method according to claim 9, characterized in that in step S6, the preheating temperature is 400 to 550°C, the preheating time is 0.5 hours or more, and the temperature of the molten zinc plating solution used during the molten zinc plating is 400 to 530°C.

11. The manufacturing method according to claim 9, characterized in that the thickness of the zinc plating layer is 10 to 150 μm, preferably 40 to 150 μm.

12. The manufacturing method according to claim 9, characterized in that the microstructure of the chain steel in the chain obtained in step S6 is tempered martensite and carbides finely dispersed between the lamellae.

13. The performance of the chain satisfies yield strength Rp 0.2 ≥ 1050 MPa, tensile strength R m ≥ 1200 MPa, elongation A ≥ 14%, reduction of area Z ≥ 50%, and Charpy impact absorbed energy A at -20°C kv ≥ 60 J, and the corrosion rate after 120 h of 5% NaCl neutral salt spray corrosion test is less than 0.2 g / m 2 ·h, the manufacturing method according to claim 9.